Alkyl-quinolone-dependent quorum sensing controls prophage-mediated autolysis in Pseudomonas aeruginosa colony biofilms - Giallonardi, Giulia; Letizia, Morgana; Mellini, Marta; Frangipani, Emanuela; Halliday, Nigel; Heeb, Stephan; Cámara, Miguel; Visca, Paolo; Imperi, Francesco; Leoni, Livia; Williams, Paul; Rampioni, Giordano (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa is a model quorum sensing (QS) pathogen with three interconnected QS circuits that control the production of virulence factors and antibiotic tolerant biofilms. The pqs QS system of P. aeruginosa is responsible for the biosynthesis of diverse 2-alkyl-4-quinolones (AQs), of which 2-heptyl-4-hydroxyquinoline (HHQ) and 2-heptyl-3-hydroxy-4(1H)-quinolone (PQS) function as QS signal molecules. Transcriptomic analyses revealed that HHQ and PQS influenced the expression of multiple genes via PqsR-dependent and -independent pathways whereas 2-heptyl-4-hydroxyquinoline N-oxide (HQNO) had no effect on P. aeruginosa transcriptome. HQNO is a cytochrome bc1 inhibitor that causes P. aeruginosa programmed cell death and autolysis. However, P. aeruginosa pqsL mutants unable to synthesize HQNO undergo autolysis when grown as colony biofilms. The mechanism by which such autolysis occurs is not understood. Through the generation and phenotypic characterization of multiple P. aeruginosa PAO1 mutants producing altered levels of AQs in different combinations, we demonstrate that mutation of pqsL results in the accumulation of HHQ which in turn leads to Pf4 prophage activation and consequently autolysis. Notably, the effect of HHQ on Pf4 activation is not mediated via its cognate receptor PqsR. These data indicate that the synthesis of HQNO in PAO1 limits HHQ-induced autolysis mediated by Pf4 in colony biofilms. A similar phenomenon is shown to occur in P. aeruginosa cystic fibrosis (CF) isolates, in which the autolytic phenotype can be abrogated by ectopic expression of pqsL.